VD_FINDINFO HC / 2010 / 496 vom 23. September 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, BAIL À LOYER, DEMEURE DU DÉBITEUR, LOYER, LOGEMENT | 101 CO, 257d CO, 273 al. 1 CO, 457 al. 1 CPC, 9 Cst., 23 al. 2 LPEBL, 7 LPEBL, 9 LPEBL